Mathematically forecasting for generalized business by using fuzzy trapezoidal numbers - Khatun, Fatema; Hossain, Md Sahadat (Journal of Bangladesh Academy of Sciences, 2022)
In this paper, we forecasted the future of a business by using fuzzy trapezoidal numbers and the fuzzy Delphi method. This result is compared with another result obtained using the fuzzy triangular numbers and Delphi method. At last, we see that our method is more general than others. J. Bangladesh Acad. Sci. 45(2); 147-154: December 2021